Peptidase neurolysin functions to preserve the brain after ischemic stroke in male mice - Jayaraman, Srinidhi (J Neurochem, 2019)
Previous studies documented upregulation of peptidase neurolysin (Nln) after brain ischemia, however the significance of Nln function in the post-stroke brain remained unknown. The aim of this study was to assess the functional role of Nln in the brain after ischemic stroke. Administration of a specific Nln inhibitor Agaricoglyceride A (AgaA) to mice after stroke in a middle cerebral artery occlusion model (MCAO), dose-dependently aggravated injury measured by increased infarct and edema volumes, blood-brain barrier disruption, increased levels of IL-6 and MCP-1, neurological and motor deficit 24 h after stroke. In this setting, AgaA resulted in inhibition of Nln in the ischemic hemisphere leading to increased levels of Nln substrates bradykinin, neurotensin and substance P. AgaA lacked effects on several physiological parameters and appeared non-toxic to mice. In a reverse approach, we developed an adeno-associated viral vector (AAV2/5-CAG-Nln) to overexpress Nln in the mouse brain. Applicability of AAV2/5-CAG-Nln to transduce catalytically active Nln was confirmed in primary neurons and in vivo. Overexpression of Nln in the mouse brain was also accompanied by decreased levels of its substrates. Two weeks after in vivo transduction of Nln using the AAV vector, mice were subjected to MCAO and the same outcome measures were evaluated 72 h later. These experiments revealed that abundance of Nln in the brain protects animals from stroke. This study is the first to document functional significance of Nln in pathophysiology of stroke and provide evidence that Nln is an endogenous mechanism functioning to preserve the brain from ischemic injury.